Enhancing the Capacity of Muslim Women MSMEs through Digital Marketing Training and Halal Product Certification - Sufyati HS, Sufyati HS; Handayani, Tati; Septyan, Krisno; Karimah, Diva Azka; Shafwan, Muhammad Alif (Amalee: Indonesian Journal of Community Research and Engagement, 2025)
The entrepreneurial capacity of Muslim women at the Berlian Cooperative in South Tangerang remains limited, particularly in terms of digital marketing skills and understanding of halal product standards. Most of their businesses operate on a micro-scale with limited market reach and do not fully comply with comprehensive halal standards, hampering their competitiveness and sustainability. The purpose of this community service was to improve their knowledge of halal standards and digital marketing skills as a promotional and information dissemination tool. The service adopted a Participatory Rural Appraisal (PRA) approach, which included outreach, education, training, and direct mentoring for selected cooperative members through purposive sampling. The results of the service demonstrated a significant increase in participants' understanding of halal certification, application procedures, and the implementation of halal standards in production. Participants were able to identify halal and thayyib ingredients and align their production practices with Islamic principles. In the area of digital marketing, participants successfully created business social media accounts, utilized digital platforms for promotion, and developed engaging content to effectively engage consumers. Future community service programs should expand the implementation period, provide comprehensive halal certification guidance, and integrate digital business tools to ensure greater sustainability and broader impact.